Sistema de transmisión de datos a través de la radio FM aplicando técnicas de Datos sobre Sonido. - Leonardo Rentería; José Jínez; Klever Torres; Jéssica Ramos (NOVASINERGIA, 2023)
In Ecuador, Internet access has been considered an essentialservice since 2015; however, only 60% of its population has access. 70% of Ecuadorians in urban areas have Internet access, whereas only 38% in rural areas do. In this sense, this work aimedto design and implement a text and image transmission system through traditional FM radio based on data-over-sound technology so that it can be used as a tool to reduce the digital divide in rural areas. A transmitter and a receiver prototype were built, and the data was encoded using the BPSK modulation technique and sent at different transmission rates: 4800, 9600, 19200, 76800, and 11500 bits per second (bps).The error rate was measuredto evaluate the operation of the device, defined as the ratio between the number of bits transmitted and the number of bits received. As a result, a minimum error rate of 58% was obtained at a speed of 4800 bps and a maximum of 61.25% at 115200 bps; likewise, the system allowed images of up to 256 pixels to be sent. Unlike other related works, this proposal will not only exceed the coverage distancebut can also be implemented on an existing broadcasting infrastructure to reach the most vulnerable.